The Influence of Achievement Motivation, Time Management, and Social Support on the Academic Achivement of Working Students - Rachmat Sidi Mawardi; Basilius Redan Werang; Ni Luh Gede Erni Sulindawati (LPPM Undiksha, 2026)
This study is motivated by the variability in academic achievement among working-class students and the suboptimal role of achievement motivation, time management, and social support in supporting learning success. In addition, limited study time due to occupational demands is presumed to influence students’ academic performance. This study aims to examine the effects of achievement motivation, time management, and social support on the academic achievement of working-class students, both partially and simultaneously. This research employed an ex-post facto design involving 162 working-class students at STIE Indocakti. Data were collected through questionnaires and documentation, and analyzed using simple regression, multiple regression, and partial correlation techniques. The results indicate that achievement motivation, time management, and social support have positive and statistically significant effects on academic achievement, both individually and collectively. These findings suggest that strengthening motivational development programs, providing time management training, and enhancing institutional and workplace social support are essential strategies for improving the academic performance of working-class students. In conclusion, the synergy between internal and external factors plays a crucial role in enhancing the academic achievement of working-class students.